Development of an electronic nose for determining the freshness of fish by the desorption constants of sensors - Vorobioff, Juan; Rodriguez, Daniel Fabian; Boggio, Norberto Gabriel; Rinaldi, Carlos Alberto (American Scientific Publishers, 2013)
Fil: Vorobioff, Juan. Comisión Nacional de Energía Atómica; Argentina